2020
DOI: 10.1057/s41292-020-00209-1
|View full text |Cite|
|
Sign up to set email alerts
|

Concussion killjoys: CTE, violence and the brain’s becoming

Abstract: CTE, or chronic traumatic encephalopathy, is caused by repetitive head trauma and detected by a distinctive stain for a protein called ‘tau’ in autopsied brain tissue. While the number of diagnosed patients is only in the hundreds, the cultural footprint of the disease in North America is huge, both because those diagnosed are often celebrity-athletes and because millions of children, adolescents and young men and women play collision sports like football and hockey. We argue that the widespread attention to C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Grano further argues that the social values and conceptions of risk embedded within brain banking are unlikely to do justice to classed and raced aspects of risk-based decision making that are key to understanding the concussion crisis. Others (e.g., Brayton et al, 2019;Henne and Ventresca, 2019;Martin and McMillan, 2020) have likewise identified reductionist and/or neoliberal logics underpinning reporting into the concussion crisis; a conclusion that chimes with existing research suggesting that neuroscientific findings frequently perpetuate rather than challenge existing understandings of society (O'Connor et al, 2012;O'Connor and Joffe, 2013). These conclusions regarding the underpinning logics of concussion science and journalism are complementary to, and yet notably distinct from, those that consider overt conflicts of interest.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Grano further argues that the social values and conceptions of risk embedded within brain banking are unlikely to do justice to classed and raced aspects of risk-based decision making that are key to understanding the concussion crisis. Others (e.g., Brayton et al, 2019;Henne and Ventresca, 2019;Martin and McMillan, 2020) have likewise identified reductionist and/or neoliberal logics underpinning reporting into the concussion crisis; a conclusion that chimes with existing research suggesting that neuroscientific findings frequently perpetuate rather than challenge existing understandings of society (O'Connor et al, 2012;O'Connor and Joffe, 2013). These conclusions regarding the underpinning logics of concussion science and journalism are complementary to, and yet notably distinct from, those that consider overt conflicts of interest.…”
Section: Discussionmentioning
confidence: 81%
“…The story of Omalu and Webster has also shaped societal understandings of CTE and concussion, in particular through the book League of Denial (Fainaru-Wada and Fainaru, 2013 ) and the film Concussion (Landesman, 2015 ), both of which center Omalu in the story of CTE. Ventresca has argued that these are the “key media texts” to have “crucially shaped” the “underlying tone of media coverage about CTE” ( 2019 , p. 143) while Martin and McMillan describe Concussion as having “solidified star status for the fragile brain” (Martin and McMillan, 2020 , p. 2). According to Sandel, Concussion may even have resulted in a drop in the popularity of the NFL (Sandel, 2020 , p. 170).…”
Section: Introduction: When Omalu Met Webstermentioning
confidence: 99%
“…Starring Will Smith as Omalu; David Morse as Webster; and Alec Baldwin as Julian Bailes, a well-known neurosurgeon and former doctor to the Pittsburgh Steelers, Concussion is a fictionalized retelling of the story underpinning the introduction this essay – Omalu’s (re)discovery of CTE. The film occupies a central place in ongoing discourse about CTE: It has prompted articles in The Lancet Neurology ( Smith and Stewart, 2016 ), while social scientists have argued that it has ‘solidified star status for the fragile brain’ ( Martin and McMillan, 2020 : 2). Alongside League of Denial , the film is understood as one of the ‘key media texts’ to have ‘crucially shaped’ the ‘underlying tone of media coverage about CTE’ ( Ventresca, 2019 : 143).…”
Section: Discussionmentioning
confidence: 99%
“…Increasingly, though, I deem my sociological will‐to‐reflexivity as inadequate. Am I not complicit in perpetuating—and for the same mundane, methodological reasons—the heteronormative and potentially performative effects of research that continues to construct CTE as a problem that, first, overwhelmingly affects men and, second, locates women in the discussion primarily as caregivers to afflicted partners (Martin & McMillan, 2020)? Does this not demand redress, and not just reflexivity?…”
Section: Approaching Complicitymentioning
confidence: 99%